2015
DOI: 10.1039/c5ra01821h
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on the activation mechanism involving bifunctional tertiary amine–thioureas and isatylidene malononitriles

Abstract: DFT studies on the activation mechanism of the Michael addition reactions containing bifunctional tertiary amine–thioureas and isatylidene malononitriles have been performed at the B3LYP/6-311++G(d,p)//B3LYP/6-31G(d) level of theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Recently, we reported the reaction mechanism of an asymmetric conjugate addition of dimethyl phosphites to isatylidene malononitriles catalyzed by bifunctional tertiary amine−thiourea. 24 As a continuation of our interests in investigating the mechanism of organocatalytic asymmetric reactions, herein we report the mechanisms of the quininesquaramide catalyzed aza-Friedel−Crafts (aza-F−C) reaction between cyclic trifluoromethyl ketimine and naphthol (Scheme 1). 25…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported the reaction mechanism of an asymmetric conjugate addition of dimethyl phosphites to isatylidene malononitriles catalyzed by bifunctional tertiary amine−thiourea. 24 As a continuation of our interests in investigating the mechanism of organocatalytic asymmetric reactions, herein we report the mechanisms of the quininesquaramide catalyzed aza-Friedel−Crafts (aza-F−C) reaction between cyclic trifluoromethyl ketimine and naphthol (Scheme 1). 25…”
Section: ■ Introductionmentioning
confidence: 99%
“…On the basis of experimental data, a plausible transition state model for the oxa-Michael step of the nucleophilic epoxidation is illustrated in Figure . The alkylidene­malono­nitrile is activated and oriented by a H-bonding network of the thiourea NH and the OH bonds . The OH group of the CHP is expected to be strongly engaged in H-bonding interaction with the basic quinuclidine nitrogen.…”
mentioning
confidence: 99%
“…16 However, synthetic approaches to differently substituted 1,2-dicarbonyl compounds are usually step intensive and typically involve redox approaches. Other synthetic approaches have been reported to circumvent this limitation; for example, Antoniotti et al reported the There are many reports that describe one-pot procedures to obtain quinoxalines from different starting materials, such as 1,2-diols, 19 alkynes 20 or arylallenes. 21 However, all these procedures are suspect to involve the in situ formation of diketone followed by condensation with o-phenylenediamine, since all of them need oxidative conditions and the use of organometallic catalysts, such as ruthenium or gold.…”
Section: Quinoxalinesmentioning
confidence: 99%
“…20 The first one is limited to symmetrically substituted pyrazines and sometimes instability of α-amino aldehydes intermediates to certain conditions limits the scope of the reaction. The latter shares the same main limitation as quinoxaline-synthesis procedures, i.e.…”
Section: Pyrazinesmentioning
confidence: 99%